Self initiated polymerization of methyl methacrylate using atom teransfer radical polymerization method - 383131 Hanim Hafizah Mazlan; Ahmedy Abu Naim, supervisor; Fakulti Sains (2008)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2008